HYGINE SANITASI SANGAT PENTING UNTUK MEMPERTAHANKAN KUALITAS AIR MINUM DEPO ISI ULANG DI KABUPATEN LOMBOK TIMUR - Karjono Karjono; Silvia Ni Nyoman Sintari (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze the relationship between sanitary hygiene and storage time with the quality of refill drinking water in East Lombok Regency. This study used a cross-sectional design. The population in this study is 101 drinking water stations recorded in 2022. A sample of 50 refill stations is taken using simple random sampling. The independent variables are sanitary hygiene and storage time with water quality as the dependent variable. Data were analyzed univariately and bivariately with computer aids. Most of the drinking water stations met sanitary hygiene requirements which are indicated in the station place, equipment used, handlers and sources of raw water by 28 (56%) with a storage time of more than three days (90%). Most of the drinking water refill stations which have of a quality indicated by PH more than 500 were 34 (68%). There is a significant relationship between the sanitation hygiene of stations and the quality of drinking water stations in East Lombok Regency in 2022. There is a significant relationship between hygiene sanitation stations and the quality of drinking water stations in East Lombok Regency in 2022. It is suggested to the Head of Health Office in East Lombok Regency through the sanitarian sub-sector to carry out periodic sanitation inspections to maintain sanitation hygiene of drinking water stations so that the quality of drinking water is maintained.